The fall of Fergal, or, Not so dingly in the Dell - Ardagh, Philip; Roberts, David, 1970- (New York : Henry Holt, 2004)
When Le Fay McNally becomes a finalist in the "Tap 'n' Type" typewriting competition, she and her four unusual siblings stay at the Dell Hotel, where they encounter joy, tragedy, and a variety of interesting characters.
G10
Keywords: Brothers and sisters -- Fiction; Contests -- Fiction; Hotels, motels, etc. -- Fiction; Typewriting -- Fiction; Humorous stories